Study of the rainfall in the bioregión the Mountain range of the Central Coast, Venezuela (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2021)
Global warming, which in turn is causing climate change that is having a dramatic impact on the economy, communities and ecosystems, causing serious economic, human and biodiversity losses. The poorest countries, the least prepared to face rapid climate changes, will be the ones that will suffer the worst consequences of the phenomenon. Climate change can be seen in the environment, it is causing changes in the hydrological cycle in some regions of Latin America, with changes in rainfall in an irregular and unpredictable way. In Venezuela, global climate models suggest a general decrease in rainfall. A decrease in the collection of water whose main source is the basins, would affect its availability for human consumption and for irrigation purposes, affecting treatment costs and limiting the development of communities. Therefore, it was decided to study the influence of climate change on the behavior of rainfall in the Cordillera de la Costa bioregion, in that area there are important cities in the center of the country, where industrial and agricultural activities are developed. It also has 6 national parks. The meteorological data studied was based on the information provided by the National Institute of Meteorology and Hydrology (INAMEH), although only 10 meteorological stations, out of 20 pluviometric stations located in the bioregion, presented 30 years of continuous registration, due to serious deficiencies. registration or inoperability. Descriptive and inferential statistical analyzes were applied to the historical series, finding that they are seasonal series and required the application of autocorrelations and ARIMA models, validated by the Ljung-Box test, based on the portmanteau test, the Mann Kendall test and the slope of Sen. It was determined that the behavior of the studied rainfall is not influenced by climate change.
Keywords: Climate change; rainfall; bioregion; ARIMA